Structure design and simulation analysis of the water surface cleaning robot. Issue 1 (1st January 2022) - Wang, Pei; Fu, Yupeng; Yang, Hang; Peng, He; Wang, Hetao; Ding, Rongtao
Abstract: In order to effectively carry out water management and reduce people's labor intensity, a double-hull water surface garbage cleaning robot is designed, using a pair of adjustable speed pump propellers to provide driving and steering power to the robot. It identifies the water surface garbage position through the binocular camera and algorithm, and the linkage mechanism is designed to complete the garbage pickup function. Through the Raspberry Pi as a controller, the robot has an autonomous intelligent recognition function and an autonomous recovery system. The kinematic simulation analysis shows that the robot garbage picks quickly and accurately; through the prototype function test, the robot is suitable for various complex water environment, with high operation efficiency and reliable performance, and can be widely used in water management.